1987
DOI: 10.1111/j.1755-3768.1987.tb07038.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an elastic model in the pathogenesis of keratoconus

Abstract: One eye of 27 patients with keratoconus and 37 normals were examined by photokeratoscopy and topographic pachometry to obtain comparative informations about the corneal shape and thickness profile, characterized by radius of the central curvature K, the coefficient of radius variation RV, the central corneal thickness T and the coefficient of thickness variation TV. RV and TV express the corneal central-peripheral variation in radius of curvature and thickness, respectively. Compared with normals the keratocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…Preliminary analyses were performed to ensure no violation of the assumptions of normality, linearity and homoscedasticity. Figures 3,4,5,6,7,8 show the relationships between corneal parameters (CCT, Km and Astig.) and ORA parameters (CH and CRF) in normal and keratoconic eyes before treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Preliminary analyses were performed to ensure no violation of the assumptions of normality, linearity and homoscedasticity. Figures 3,4,5,6,7,8 show the relationships between corneal parameters (CCT, Km and Astig.) and ORA parameters (CH and CRF) in normal and keratoconic eyes before treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A significant limitation of these studies was that most of them were performed in vitro. Edmund et al [8] compared the viscoelasticity of keratoconic and normal eyes, and found that the distensibility of eyes was higher in normal eyes, so they concluded that distensibility may be an important factor in the pathogenesis of keratoconus. The same research group reported [14] that corneal rigidity tends to be lower in keratoconus, and concluded that a decrease in the corneal matrix and in the corneal tissue mass might be an important pathogenic factor in the development of keratoconus.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Corneal transplantation is the best and most successful surgical option for advanced keratoconus, a stage where management with all other modalities fails. 6 Although the ectatic area of the cornea is generally displaced inferiorly, [7][8][9] the corneal irregularities lead to vision problems even in the early stages of the condition. Contact lens intolerance, decreased vision and/or central corneal scarring accounts for 10-25% of those keratoconus patients undergoing penetrating keratoplasty.…”
Section: Introductionmentioning
confidence: 99%